Preparation method of Li3Mg2SbO6 ceramic with improved sintering characteristic and microwave dielectric property

By using Sb2O5 as raw material and employing ball milling, pre-firing, cold isostatic pressing, and high-temperature sintering processes, the sintering characteristics and microwave dielectric properties of Li3Mg2SbO6 ceramics were solved, and microwave dielectric ceramics with high density, low dielectric constant, and near-zero τf value suitable for 5G communication were prepared.

CN121292942APending Publication Date: 2026-01-09SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511349689.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing Li3Mg2SbO6 ceramics suffer from poor sintering characteristics and unsatisfactory microwave dielectric properties during preparation. In particular, the cracking and deterioration of dielectric properties caused by the volatility of Sb2O3 and valence mismatch limit its practical application.

Method used

Using Sb2O5 as raw material, and combining ball milling, pre-firing, cold isostatic pressing and high-temperature sintering processes, pure-phase crack-free Li3Mg2SbO6 microwave dielectric ceramics were prepared. By controlling the volatilization loss and compositional stability during the high-temperature reaction process, the sintering characteristics and dielectric properties were optimized.

Benefits of technology

The prepared Li3Mg2SbO6 ceramic material is a pure phase without cracks, with high density, and has microwave dielectric properties with low dielectric constant, high Qf and near-zero τf values, making it suitable as a key material in 5G communication technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121292942A_ABST
    Figure CN121292942A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of Li3Mg2SbO6 ceramic with improved sintering characteristic and microwave dielectric property, which comprises the following steps: weighing Li2CO3, MgO and Sb2O5 according to the stoichiometric ratio of the general chemical formula Li3Mg2SbO6, mixing, ball-milling until the materials are uniformly mixed, drying and sieving to obtain a primary ball-milled material; the primary ball-milled material is placed in a box-type furnace for high-temperature presintering, the presintering temperature is 800-1000 DEG C, the presintering time is 2-6 hours, and secondary ball-milled material is obtained after ball milling, drying and sieving are conducted again; performing cold isostatic pressing on the secondary ball-milled material to obtain a ceramic green body; the ceramic green body is placed in a box-type furnace for high-temperature sintering, the sintering temperature ranges from 1350 DEG C to 1500 DEG C, the sintering time ranges from 2 hours to 6 hours, and the Li3Mg2SbO6 microwave dielectric ceramic is obtained. The preparation process is simple, the sintering characteristic of the ceramic is improved, the obtained microwave dielectric ceramic is a pure phase, the density is relatively high, and the commercialization of Li3Mg2SbO6 ceramic is favorably realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of functional materials, and relates to a preparation method of a microwave dielectric ceramic material, in particular to a preparation method of Li3Mg2SbO6 ceramic for improving sintering characteristics and microwave dielectric properties. BACKGROUND

[0002] As an important functional ceramic material, microwave dielectric ceramics are essential dielectric elements in microwave circuits and are key strategic materials in modern communication technology. Despite the importance of microwave dielectric properties in advanced technologies such as 5G communication, radar systems, and satellite communication, there are still major challenges in optimizing microwave dielectric properties and developing new compositions. The challenges include (1) further improving the quality factor (Qf) to increase frequency selectivity, (2) further reducing the relative dielectric constant (ε r ) to increase the speed of signal propagation and reduce cross-coupling effects, and (3) achieving a near-zero resonance frequency temperature coefficient (τ f ) to ensure the thermal stability of communication equipment. Therefore, it is crucial to develop new materials with low dielectric constant, high Qf, and near-zero τ f value.

[0003] In recent years, lithium-based microwave dielectric ceramic materials have received increasing attention due to their outstanding dielectric properties. In particular, Li3Mg2SbO6 ceramic synthesized by a two-step solid-state method has become a promising candidate material due to its low dielectric constant and small negative τ f value. Although it has achieved good performance, this method prolongs the preparation time and increases the overall cost. Therefore, for practical applications, there is an urgent need to develop simplified and efficient manufacturing processes that achieve cost-effectiveness and high production efficiency without compromising the dielectric properties of the material. According to previous literature, Li3Mg2SbO6 ceramic synthesized by the mixed oxide route with Sb2O3 as the antimony source exhibits poor sintering characteristics (exhibiting cracking) and unsatisfactory microwave dielectric properties (Qf = 49 000 GHz, τ f = -18 ppm / ℃), which limits its practical applicability. This problem can be attributed to the volatility of Sb2O3 raw materials and the mismatch between the valence of antimony and the nominal ceramic Li3Mg2SbO6 composition, which can lead to composition deviation and volume change during high-temperature reactions, resulting in deterioration of sintering characteristics and dielectric properties. In addition, in industrial production, the selection and pretreatment of raw materials play a crucial role in determining the dielectric properties of the final product. Therefore, whether the sintering characteristics and microwave dielectric properties of Li3Mg2SbO6 ceramic can be improved by changing the raw materials is a technical problem worthy of research for those skilled in the art. SUMMARY

[0004] In view of the deficiencies of the prior art, the purpose of the present application is to provide a preparation method of Li3Mg2SbO6 ceramic with improved sintering characteristics and microwave dielectric properties, which selects Sb2O5 raw material to minimize volatilization loss and stabilize valence during the sintering process to reduce volume change during the high-temperature reaction process, and the prepared Li3Mg2SbO6 microwave dielectric ceramic material is pure phase without cracking, has higher density, and has microwave dielectric properties of low dielectric constant, high Qf and near-zero τ f .

[0005] In order to achieve the above-mentioned purpose, the present application adopts the following technical solutions to achieve the above-mentioned purpose:

[0006] A preparation method of Li3Mg2SbO6 ceramic with improved sintering characteristics and microwave dielectric properties, comprising the following steps:

[0007] Step one, according to the stoichiometric ratio of metal elements in the chemical formula Li3Mg2SbO6, Li2CO3, MgO and Sb2O5 are weighed and mixed, ball milled to uniform mixing, dried and sieved to obtain a first ball mill;

[0008] Step two, the first ball mill is placed in a box furnace for high-temperature pre-sintering, the pre-sintering temperature is 800-1000 DEG C, the pre-sintering time is 2-6h, and the second ball mill is obtained after ball milling, drying and sieving;

[0009] Step three, the second ball mill is cold isostatic pressed to form a ceramic green body;

[0010] Step four, the ceramic green body is placed in a box furnace for high-temperature sintering, the sintering temperature is 1350-1500 DEG C, the sintering time is 2-6h, and the Li3Mg2SbO6 microwave dielectric ceramic is obtained.

[0011] The present application also has the following technical features:

[0012] Preferably, the ball milling in step one and step two is carried out in a planetary ball mill with anhydrous ethanol as the medium at a rotation speed of 400r / min for 6-10h.

[0013] Preferably, the drying in step one and step two is carried out in an oven at 60-80 DEG C for 8-10h.

[0014] Preferably, the sieving in step one and step two is carried out through an 80-200 mesh sieve.

[0015] Preferably, the pressure of the cold isostatic pressing in step three is 200MPa.

[0016] Compared with the prior art, the present application has the following technical effects:

[0017] The microwave dielectric ceramic material Li3Mg2SbO6 prepared by the method has pure phases and no cracking, and has high density and microwave dielectric properties of low dielectric constant, high Qf and near-zero τ f When the sintering temperature is 1450 DEG C, the density of the ceramic material is 90%, and balanced microwave dielectric properties are obtained: epsilon r = 9.93, Qf = 61 076 GHz (f0 = 9.55 GHz), tau f = -5.60 ppm / DEG C; the microwave dielectric ceramic material prepared by the method is used for preparing microwave electronic components, can be used as a key material for solving the problem of 5G communication technology, and has great application value in industrial production. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 XRD patterns of the microwave dielectric ceramic materials prepared in Examples 1-5;

[0019] Figure 2 Sample physical pictures of the microwave dielectric ceramic materials prepared in Examples 1-5;

[0020] Figure 3 Relative density diagrams of the microwave dielectric ceramic materials prepared in Examples 1-5;

[0021] Figure 4 Microwave dielectric properties of the microwave dielectric ceramic materials prepared in Examples 1-5. DETAILED DESCRIPTION

[0022] The specific content of the application is further explained in detail in combination with the examples.

[0023] The raw materials Li2CO3, MgO and Sb2O5 used in the application have purities of 99.99%, 99.99% and 99.95%, respectively.

[0024] Example 1

[0025] Step one, according to the stoichiometric ratio of metal elements in the chemical formula Li3Mg2SbO6, Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively are mixed, and the mixture is ball milled in a planetary ball mill at a speed of 400 r / min for 8 h with anhydrous ethanol as a medium to obtain a uniformly mixed slurry, and the ball milled slurry is placed in an oven and dried at 80 DEG C for 8 h to obtain dry primary ball mill;

[0026] Step two, the primary ball mill obtained in step one is placed in a box furnace for high temperature pre-sintering, the pre-sintering temperature is 900℃, and the pre-sintering time is 4h to obtain single-phase Li3Mg2SbO6. The secondary ball mill is obtained by ball milling the mixed slurry in a planetary ball mill at a speed of 400r / min for 8h with anhydrous ethanol as a medium, and then drying the slurry in an oven at 80℃ for 8h and passing it through a 200-mesh sieve.

[0027] Step three, the dry secondary ball mill obtained in step two is subjected to column pressing and cold isostatic pressing at a pressure of 200MPa to obtain a ceramic green body. The ceramic green body is placed in a box furnace for sintering at 1375℃ for 5h to obtain a Li3Mg2SbO6 ceramic material.

[0028] Example 2

[0029] Step one, Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively are mixed according to the stoichiometric ratio of the metal elements in the chemical formula Li3Mg2SbO6. The mixed slurry is obtained by ball milling in a planetary ball mill at a speed of 400r / min for 8h with anhydrous ethanol as a medium, and then drying the slurry in an oven at 80℃ for 10h to obtain a dry primary ball mill.

[0030] Step two, the primary ball mill obtained in step one is placed in a box furnace for high temperature pre-sintering, the pre-sintering temperature is 900℃, and the pre-sintering time is 4h to obtain single-phase Li3Mg2SbO6. The secondary ball mill is obtained by ball milling the mixed slurry in a planetary ball mill at a speed of 400r / min for 8h with anhydrous ethanol as a medium, and then drying the slurry in an oven at 80℃ for 10h and passing it through a 200-mesh sieve.

[0031] Step three, the dry secondary ball mill obtained in step two is subjected to column pressing and cold isostatic pressing at a pressure of 200MPa to obtain a ceramic green body. The ceramic green body is placed in a box furnace for sintering at 1375℃ for 5h to obtain a Li3Mg2SbO6 ceramic material.

[0032] Example 3

[0033] Step one, Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively are mixed according to the stoichiometric ratio of the metal elements in the chemical formula Li3Mg2SbO6. The mixed slurry is obtained by ball milling in a planetary ball mill at a speed of 400r / min for 8h with anhydrous ethanol as a medium, and then drying the slurry in an oven at 80℃ for 10h to obtain a dry primary ball mill.

[0034] Step 2: The primary ball milling material obtained in Step 1 is placed in a box furnace for high-temperature pre-calcination at 900℃ for 4 hours to obtain single-phase Li3Mg2SbO6. The mixture is then ball-milled in a planetary ball mill at 400 r / min for 6 hours using anhydrous ethanol as the medium to obtain a mixed slurry. The ball-milled slurry is then placed in an oven and dried at 60℃ for 8 hours before being passed through a 100-mesh sieve to obtain the dried secondary ball milling material.

[0035] Step 3: The dried secondary ball milling material obtained in Step 2 is pressed into a column using a mold and then cold isostatically pressed at a pressure of 200 MPa to obtain a ceramic green body. The pressed ceramic green body is placed in a box furnace and sintered at 1425℃ for 5 hours to obtain Li3Mg2SbO6 ceramic material.

[0036] Example 4

[0037] Step 1: According to the stoichiometric ratio of the metal elements in the general chemical formula Li3Mg2SbO6, take Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively, mix them, and ball mill them in a planetary ball mill at a speed of 400 r / min for 10 h with anhydrous ethanol as the medium to obtain a uniformly mixed slurry. Place the ball-milled slurry in an oven and dry it at 70℃ for 9 h to obtain the dried primary ball milling material.

[0038] Step 2: The primary ball milling material obtained in Step 1 is placed in a box furnace for high-temperature pre-calcination at 800℃ for 6 hours to obtain single-phase Li3Mg2SbO6. The mixture is then ball-milled in a planetary ball mill at 400 r / min for 10 hours using anhydrous ethanol as the medium to obtain a mixed slurry. The ball-milled slurry is then placed in an oven and dried at 70℃ for 9 hours before being passed through a 150-mesh sieve to obtain the dried secondary ball milling material.

[0039] Step 3: The dried secondary ball milling material obtained in Step 2 is pressed into a column using a mold and then cold isostatically pressed at a pressure of 200 MPa to obtain a ceramic green body. The pressed ceramic green body is placed in a box furnace and sintered at 1450℃ for 4 hours to obtain Li3Mg2SbO6 ceramic material.

[0040] Example 5

[0041] Step 1: According to the stoichiometric ratio of the metal elements in the general chemical formula Li3Mg2SbO6, take Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively, mix them, and ball mill them in a planetary ball mill at a speed of 400 r / min for 6 hours with anhydrous ethanol as the medium to obtain a uniformly mixed slurry. Place the ball-milled slurry in an oven and dry it at 80℃ for 8 hours to obtain the dried primary ball milling material.

[0042] Step 2: The primary ball milling material obtained in Step 1 is placed in a box furnace for high-temperature pre-calcination at 1000℃ for 2 hours to obtain single-phase Li3Mg2SbO6. The mixture is then ball-milled in a planetary ball mill at 400 r / min for 6 hours using anhydrous ethanol as the medium to obtain a mixed slurry. The ball-milled slurry is then placed in an oven and dried at 80℃ for 8 hours before being passed through an 180-mesh sieve to obtain the dried secondary ball milling material.

[0043] Step 3: The dried secondary ball milling material obtained in Step 2 is pressed into a column using a mold and then cold isostatically pressed at a pressure of 200 MPa to obtain a ceramic green body. The pressed ceramic green body is placed in a box furnace and sintered at 1475℃ for 4 hours to obtain Li3Mg2SbO6 ceramic material.

[0044] Example 6

[0045] Step 1: According to the stoichiometric ratio of the metal elements in the general chemical formula Li3Mg2SbO6, take Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively, mix them, and ball mill them in a planetary ball mill at a speed of 400 r / min for 6 hours with anhydrous ethanol as the medium to obtain a uniformly mixed slurry. Place the ball-milled slurry in an oven and dry it at 80℃ for 8 hours to obtain the dried primary ball milling material.

[0046] Step 2: The primary ball milling material obtained in Step 1 is placed in a box furnace for high-temperature pre-calcination at 1000℃ for 2 hours to obtain single-phase Li3Mg2SbO6. The mixture is then ball-milled in a planetary ball mill at 400 r / min for 6 hours using anhydrous ethanol as the medium to obtain a mixed slurry. The ball-milled slurry is then placed in an oven and dried at 80℃ for 8 hours before being passed through an 180-mesh sieve to obtain the dried secondary ball milling material.

[0047] Step 3: The dried secondary ball milling material obtained in Step 2 is pressed into a column using a mold and then cold isostatically pressed at a pressure of 200 MPa to obtain a ceramic green body. The pressed ceramic green body is placed in a box furnace and sintered at 1350℃ for 6 hours to obtain Li3Mg2SbO6 ceramic material.

[0048] Example 7

[0049] Step 1: According to the stoichiometric ratio of the metal elements in the general chemical formula Li3Mg2SbO6, take Li2CO3, MgO and Sb2O5 with purities of 99.99%, 99.99% and 99.95% respectively, mix them, and ball mill them in a planetary ball mill at a speed of 400 r / min for 6 hours with anhydrous ethanol as the medium to obtain a uniformly mixed slurry. Place the ball-milled slurry in an oven and dry it at 80℃ for 8 hours to obtain the dried primary ball milling material.

[0050] Step 2: The primary ball milling material obtained in Step 1 is placed in a box furnace for high-temperature pre-calcination at 1000℃ for 2 hours to obtain single-phase Li3Mg2SbO6. The mixture is then ball-milled in a planetary ball mill at 400 r / min for 6 hours using anhydrous ethanol as the medium to obtain a mixed slurry. The ball-milled slurry is then placed in an oven and dried at 80℃ for 8 hours before being passed through an 180-mesh sieve to obtain the dried secondary ball milling material.

[0051] Step 3: The dried secondary ball milling material obtained in Step 2 is pressed into a column using a mold and then cold isostatically pressed at a pressure of 200 MPa to obtain a ceramic green body. The pressed ceramic green body is then placed in a box furnace and sintered at 1500℃ for 2 hours to obtain Li3Mg2SbO6 ceramic material.

[0052] Figure 1 The images show the XRD patterns of the microwave dielectric ceramic materials prepared in Examples 1-5; where the horizontal axis represents the diffraction angle and the vertical axis represents the normalized diffraction peak intensity. Figure 1 The results showed that a single phase was detected in all samples across the entire sintering temperature range, with no second phase appearing, confirming the formation of the single phase.

[0053] Figure 2 The images show actual samples of the microwave dielectric ceramic materials prepared in Examples 1-5. Figure 2 All samples showed no cracks.

[0054] Figure 3 The diagram shows the relative density of the microwave dielectric ceramic materials prepared in Examples 1-5. Figure 3 The sample sintered at 1450℃ showed high density.

[0055] Figure 4 The microwave dielectric properties of the microwave dielectric ceramic materials prepared in Examples 1-5 are shown. Figure 4 The sample sintered at 1450℃ exhibits balanced microwave dielectric properties: ε r =9.93, Qf=61 076GHz (f0=9.55GHz), τ f = -5.60ppm / ℃.

[0056] Those skilled in the art will recognize that the above description is merely a preferred embodiment of the present invention and does not limit the invention. Any obvious modifications made to the present invention by those skilled in the art in conjunction with existing knowledge are within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing Li3Mg2SbO6 ceramics with improved sintering characteristics and microwave dielectric properties, characterized in that, Includes the following steps: Step 1: Weigh Li2CO3, MgO and Sb2O5 according to the stoichiometric ratio of the metal elements in the general chemical formula Li3Mg2SbO6, mix them, ball mill until uniformly mixed, and then dry and sieve to obtain primary ball milling material; Step 2: Place the primary ball milling material in a box furnace for high-temperature pre-firing at a temperature of 800-1000℃ for 2-6 hours. After ball milling, drying and sieving, secondary ball milling material is obtained. Step 3: Cold isostatically press the secondary ball milling material to obtain a ceramic green body; Step 4: Place the ceramic green body in a box furnace for high-temperature sintering at a temperature of 1350–1500℃ for 2–6 hours to obtain Li3Mg2SbO6 microwave dielectric ceramic.

2. The method for preparing Li3Mg2SbO6 ceramics with improved sintering characteristics and microwave dielectric properties as described in claim 1, characterized in that, The ball milling described in steps one and two involves using anhydrous ethanol as the medium in a planetary ball mill at a speed of 400 r / min for 6 to 10 hours.

3. The method for preparing Li3Mg2SbO6 ceramics with improved sintering characteristics and microwave dielectric properties as described in claim 1, characterized in that, The drying process described in steps one and two involves placing the item in an oven at 60–80°C and drying it for 8–10 hours.

4. The method for preparing Li3Mg2SbO6 ceramics with improved sintering characteristics and microwave dielectric properties as described in claim 1, characterized in that, The sieving mentioned in steps one and two refers to sieving through an 80-200 mesh sieve.

5. The method for preparing Li3Mg2SbO6 ceramics with improved sintering characteristics and microwave dielectric properties as described in claim 1, characterized in that, The pressure of the cold isostatic pressing mentioned in step three is 200 MPa.